2015
DOI: 10.3748/wjg.v21.i34.9999
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of antrum-preserving double tract reconstructionvsroux-en-Y reconstruction after gastrectomy for Siewert types II and III adenocarcinoma of the esophagogastric junction

Abstract: ADTR by jejunal interposition presents similar rates of tumor recurrence, metastasis and long-term survival compared with classical reconstruction with RY esophagojejunostomy; however, it offers considerably improved near-term quality of life, especially in terms of early recovery and decreased reflux esophagitis. Thus, ADTR is recommended as a worthwhile digestive tract reconstruction method for Siewert types II and III AEG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…According to the Japanese gastric cancer guidelines, total gastrectomy with D2 lymphadenectomy is the standard option for advanced gastric cancers [ 5 ]. It was reported that 60% to 70% of proximal gastric cancers are treated with chemotherapy after proximal gastrectomy with esophago-gastrostomy and antrum-preserving signal tract reconstruction [ 14 ]. In this study, some patients in both groups underwent proximal gastrectomy and esophagogastrostomy.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Japanese gastric cancer guidelines, total gastrectomy with D2 lymphadenectomy is the standard option for advanced gastric cancers [ 5 ]. It was reported that 60% to 70% of proximal gastric cancers are treated with chemotherapy after proximal gastrectomy with esophago-gastrostomy and antrum-preserving signal tract reconstruction [ 14 ]. In this study, some patients in both groups underwent proximal gastrectomy and esophagogastrostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Many reconstruction methods are meant to resist reflux, while it remains lacking consensus. A retrospective study demonstrated that double tract reconstruction is a simple and effective method in decreasing reflux esophagitis compared with Roux-en-Y [29] . It still needs RCT to provide high-grade evidence for the method.…”
Section: Reconstruction Methods For Siewert Type II Aegmentioning
confidence: 99%
“…In the case of early EGJ lesions, surgical treatment must not be tailored only based on the oncologic outcome, but it must also aid the preservation of the digestive function as much as possible. Several authors published their favorable functional results on proximal gastrectomy and double tract jejunal reconstruction [26,27].…”
Section: Early Egj Lesionsmentioning
confidence: 99%